« Ce fut a heure illicite ». Se venger de nuit dans le royaume de France à la fin du Moyen Âge - Jean-Philippe Juchs (Criminocorpus)
The practice of aristocratic feud at night in the countryside at the end of the Middle Ages is not ordinary, first of all for symbolic reasons, because of the generally negative representation of night at that time, secondly for technical reasons, because of the lack of lightening facilities. Moreover feud needs to be publicly performed, which is impossible in the middle of the night because of darkness, but can be admissible at dawn and at dusk. While night is a matter of control by the different powers in the cities of the 14th and 15th centuries and in the following centuries, it seems that controlling the night and the aristocratic violence at night in the countryside is not really a matter of concern for the King’s administration in France.